PELANGGARAN TERHADAP KETENTUAN TENTANG PEMANFAATAN SUMBER KEKAYAAN HAYATI PERIKANAN INDONESIA DI WILAYAH PERAIRAN ZONA EKONOMI EKSLUSIF DI LAUT NATUNA UTARA - Utin Rahmah Indah Pratiwi; Zulfikar Jayakusuma; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The abundance of marine biological resources and the position that borders directly with other countries with the North Natuna Sea has resulted in many foreign fishing vessels violating the provisions by utilizing biological resources without the permission of the Indonesian state. This study regarding the provisions regarding the utilization of Indonesia's fishery biological resources in the waters of the Exclusive Economic Zone in the North Natuna Sea aims to find out the provisions that are violated and the efforts made in overcoming and reducing the number of fisheries violations.This type of research can be classified in the type of sociological research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in the West Maritime Zone Bakamla, Lantamal IV Tanjung Pinang, PSDKP Batam, the Marine and Fisheries Service of the Riau Islands Province and the POLDA Dipolairud Riau Islands, while the population and sample are all parties related to the problems examined in this study, the source of the data used, primary data, secondary data, and tertiary data, data collection techniques in this study with observation and interviews.From the results of the study as follows: the provisions violated 182 foreign fishing vessels in the North Natuna Sea in the 2016-2018 period were fishing without permits, the use of prohibited fishing gear, containing protected fish. Whereas the efforts to impose strict sanctions in the form of confiscation, fines or destruction of evidence, establish cooperation with fishermen, monitoring through MSC (Monitoring, Control and Surveillance), officers conduct routine patrol and the government adopts or international regulations. While the obstacles include the lack of fleets and patrol support facilities and the small number of Fisheries PPNS that cannot cover the vast North Natuna Sea.Keywords: EEZ, Biodiversity Resources, Fisheries, Violations, UNCLOS, Foreign Fishing Vessels